Approach to the Assessment and Management of Pediatric Patients With Atopic Dermatitis: A Consensus Document. Section III: Treatment Options for Pediatric Atopic Dermatitis. Issue 5 (November 2019) - Lansang, Perla; Lam, Joseph M.; Marcoux, Danielle; Prajapati, Vimal H.; Spring, Shanna; Lara-Corrales, Irene
Because atopic dermatitis (AD) is a chronic, relapsing disease, treatment requires the use of both active therapy to control flares and preventative maintenance therapy to promote integrity of the skin barrier. In this third of four sections, important clinical considerations for the treatment of pediatric AD are reviewed. Emerging therapies in development for pediatric AD are introduced.